Dynamics of indicators of competitive activity of highly qualified wrestlers - Victor Titarenko; Yura Tropin (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to trace the dynamics of competitive performance indicators of highly qualified wrestlers. Material & Methods: the following methods were used in the study: analysis of scientific and methodological information, generalization of best practices, analysis of protocols and videos of the final fights of highly qualified Greco-Roman style wrestlers at the world championships 2017, 2018, 2019; methods of mathematical statistics. In total, an analysis was made of 81 final duel of athletes (wrestling for first and third places). Results: analysis of the competitive activity of highly qualified wrestlers at the world championships 2017, 2018, 2019 allowed us to identify 11 basic technical actions that are most often used: handspring, handspring with a hand and head grip, tackles with a back belt, back belt, counter-measures in the standing and mat, transfers to the mat, tackles with a twist and a deflection, suplex, pushing over the carpet. It was determined that at the World Championships 2017, 2018, 2019, the most performed technical actions in the stalls are handspring, and in the standing - dumping and pushing an opponent out of the carpet. Conclusions: it was found that during the study period, the effectiveness of attacks in the standing and mat, the effectiveness of the standing and mat have dynamics to improve, which positively affects the entertainment of Greco-Roman wrestling. The average bout time is reduced from 354 seconds at the 2017 World Cup to 273 seconds at the 2019 World Cup. Such a distribution of time shows that the number of fights won ahead of schedule in wrestlers increased.